miRNA transcriptome and myofiber characteristics of lamb skeletal muscle during hypertrophic growth1 - Greene, M. A.; Powell, R.; Bruce, T.; Bridges, W. C.; Duckett, S. K. (Frontiers in Genetics, 2022)
Postnatal muscle growth is achieved through hypertrophy of the muscle fibers and is impacted by the activity of satellite cells, the quiescent muscle stem cell. Several miRNAs are preferentially expressed in skeletal muscle and could provide a mechanism for increasing muscle hypertrophy through satellite cell proliferation and/or differentiation. The objectives of this study were to: 1) characterize the miRNA transcriptome of the longissimus thoracis et lumborum muscle at several developmental timepoints [gestational d 85 (PN1), 110 (PN2), 133 (PN3), postnatal d 42 (PW1), 65 (PW2), 243 (MAT)] during muscle hypertrophy in lambs, and 2) examine miR-29a, identified in sequencing to be differentially regulated across development, loss of function on satellite cell proliferation and differentiation. Muscle fiber characteristics showed drastic increases (P < 0.0001) in fiber size and alterations in muscle fiber type occur during pre and postnatal development. miRNA sequencing comparisons were performed in developmental order (PN1 vs PN2, PN2 vs PN3, PN3 vs PW1, PW1 vs PW2, PW2 vs MAT). There were 184 differentially expressed (Padj < 0.05) miRNA, 142 unique miRNA, from all 5 comparisons made. The transitional stage (PN3 vs PW1) had the largest number (115) of differentially expressed miRNA. Inhibition of miR-29a in satellite cell culture increased (P < 0.05) cell proliferation and differentiation capacity. Characterization of the miRNA transcriptome provides valuable insights into the miRNA involved in muscle fiber hypertrophy and the potential importance of the transitional period.